FORUM FOR TEACHERS OF FOREIGN LANGUAGES: GENERAL STANDARDS AND ACHIEVEMENTS OF THE END OF PRIMARY EDUCATION (Živi jezici: Journal for Foreign Languages and Literatures, 2017)
On November 1, 2017, at the Faculty of Philology of the University of Belgrade, a Forum for foreign language teachers was held, dedicated to the General Standards of Achievement for the End of Primary Education, ie the Rulebook published in the Official Gazette of RS no. 78/2017, organized by the Associassion for Foreign Languages and Literatures of Serbia.
Keywords: Primary Education; General Standards of Achievement; foreign languages